Natural Versus Man-made Forest in Nilgiris with Special Reference to Run-off, Soil Loss and Productivity - Sambaj, P.; Chinnamani, S.; Haldorai, B. (Indian Forester, 1977)
The paper present the results of investigations on run-of soil loss accumulation of leaf litter and timber yield under native vegetation cover and under plantation of Eucalypius globulus (blue-gum) employing runoff plots. It has been concluded that there was not much difference in runoff between different forest covers though a mixed plantation of blue-gum and black wattle (Acacia mearnsii) gave less run-off Litter production was nearly the same (2.315 tonns/ha/yr) in both native "Shola" forests and Eucalyptus plantations. Mixed plantion of blue-gum and wattle is preferable to pure plantation both from ehe point of view of timber production and soil and water conservation.